An Investigation of the Influence of Changing Energy Volume Densities to Produce a Complete Process Parameter Window for Selective Laser Melting of Scalmalloy - Celine Turangi; Florian Haslich; Tim Pasang (Nusantara Science and Technology Proceedings)
The scandium-zirconium modified aluminum alloy Scalmalloy is additively manufactured using Selective Laser Melting in the Renishaw AM 400 SLM machine. THE optimal SLM process parameter window concerning relative densities exceeding 99% was investigated. Scalmalloy powder was characterized concerning particle morphology, qualitative particle size distribution, and inner gas pores. Full available SLM laser power of Renishaw AM 400 SLM machine was applied to increase productivity as much as possible. Archimedes density method and metallographic cross-sections were used to determine relative densities, whereby all samples printed exceeded 99%. THE optimal SLM process parameter window for the laser power of 400W was found to be in the range of 40-110J/mm3 where scan speed is doubled compared to other literature using 200W, thus productivity is greatly increased. Microhardness testing was also performed on all samples and showed the successful suppression of Al3(Sc1-xZrx) precipitates, whereby subsequent age hardening may be performed post-process.